A method for preparing high-strength concrete based on construction waste

By performing specific treatment of recycled coarse aggregates of construction waste and preparing composite materials, the problem of low concrete strength in the prior art has been solved, and the preparation of high-strength concrete and the complete replacement of natural coarse aggregates have been achieved, and the market application prospects have been good.

CN119241166BActive Publication Date: 2025-04-22JIEXI JUTA CONCRETE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411372786.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-04-22
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

In the prior art, the concrete strength of using construction waste to produce regenerated coarse aggregate is relatively low, which is difficult to meet the needs of support and load bearing, and the replacement rate of regenerated coarse aggregate is not high.

Method used

After conventional operations such as crushing, sorting, and magnetic separation of regenerated coarse aggregates of construction waste, deionized water, polyvinyl alcohol, dopamine and hydroxylated nanosilicon dioxide were added, and ultrasonic stirring was performed with light-proof ultrasonic stirring and vacuum drying, strengthened regenerated coarse aggregates were prepared and composited with basalt fibers to form composite materials, which were used to prepare high-strength concrete.

Benefits of technology

It has achieved the preparation of high-strength concrete, excellent mechanical strength, and achieved full replacement of natural coarse aggregates, with good market application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for preparing high-strength concrete based on construction waste, and belongs to the technical field of concrete. The present invention creatively adds deionized water, polyvinyl alcohol, dopamine and hydroxylated nano-silicon dioxide in a certain mass ratio to the recycled coarse aggregate obtained after conventional operations such as crushing, sorting and magnetic separation of construction waste in sequence, and then ultrasonically stirs in a nitrogen atmosphere in the dark and dries in a vacuum in the dark. Through the bonding of polyvinyl alcohol, the drying of dopamine and the filling effect of hydroxylated nano-silicon dioxide, a new type of reinforced recycled coarse aggregate is prepared, and the composite material is compounded and coupled with basalt fiber to form a composite material. After physical blending with cementitious material, fine aggregate, fly ash, mineral powder, deionized water and water reducing agent, concrete is obtained. The concrete not only has excellent mechanical strength, but also completely replaces natural coarse aggregate, and has very good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to a method for preparing high-strength concrete based on construction waste. Background Art

[0002] Construction waste refers to various wastes generated during the construction, laying, demolition, and repair of buildings. With the increasing amount of construction waste and the growing market demand for concrete, there have been a lot of studies on the technology of using construction waste to produce recycled coarse aggregate to partially replace natural coarse aggregate for preparing concrete. However, these technologies still have certain disadvantages that limit their actual application effects. This is because the recycled coarse aggregate produced from construction waste itself has a large number of defects, such as many micro-cracks on the surface and high water absorption. Therefore, the strength of the final concrete is often low, and it is difficult to play a good supporting and load-bearing role in actual application, which seriously limits the scope of use. At the same time, in order to obtain higher strength concrete, the recycled coarse aggregate needs to be strengthened. However, even after strengthening, the replacement rate of recycled coarse aggregate is still not high. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing high-strength concrete based on construction waste. The present invention creatively adds deionized water, polyvinyl alcohol, dopamine and hydroxylated nano-silica in a certain mass ratio to the recycled coarse aggregate obtained after conventional operations such as crushing, sorting and magnetic separation of construction waste, and then performs ultrasonic stirring in a nitrogen atmosphere in the dark and drying in a vacuum in the dark. Through the bonding of polyvinyl alcohol - drying and precipitation of dopamine - filling of hydroxylated nano-silica, a new type of reinforced recycled coarse aggregate is prepared, and the composite material is compounded and coupled with basalt fiber to form a composite material. After physical blending with cementitious material, fine aggregate, fly ash, mineral powder, deionized water and water reducing agent, concrete is obtained. The concrete not only has excellent mechanical strength, but also can completely replace natural coarse aggregate, and has very good market application prospects.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing high-strength concrete based on construction waste, the preparation method comprising the following steps:

[0006] Step X: Add fine aggregate, composite material, fly ash and mineral powder to the cementitious material under the condition of contact with air, and then stir and mix at room temperature for 1-2 minutes, then add deionized water and water reducing agent, and continue to stir and mix at room temperature for 3-5 minutes, and the preparation is completed; the composite material is a mixture of reinforced recycled coarse aggregate and basalt fiber.

[0007] As a preferred technical solution of the present invention, the mass ratio of the cementitious material, the fine aggregate, the composite material, the fly ash, the mineral powder, the deionized water and the water reducing agent in step X is 270:715-720:1080-1085:100:60-62:160:9.5-10.

[0008] As a preferred technical solution of the present invention, the cementitious material in step X is cement; the cement is P·O42.5 grade cement.

[0009] As a preferred technical solution of the present invention, the fine aggregate in step X is river sand; the fineness modulus of the river sand is 2.6.

[0010] As a preferred technical solution of the present invention, the water reducer in step X is a polycarboxylate water reducer.

[0011] As a preferred technical solution of the present invention, the mass ratio of the reinforced recycled coarse aggregate to the basalt fiber in step X is 100:1-1.2.

[0012] As a preferred technical solution of the present invention, the reinforced recycled coarse aggregate in step X is prepared by the following steps:

[0013] (1) crushing, sorting, magnetic separation and screening the construction waste in sequence to obtain recycled coarse aggregate;

[0014] (2) Add 10-12 parts by weight of polyvinyl alcohol to 100 parts by weight of deionized water, and then stir at 90-95° C. until completely dissolved, cool naturally to room temperature, then add 6 parts by weight of dopamine, 0.2-0.3 parts by weight of hydroxylated nano-silica and 30-35 parts by weight of recycled coarse aggregate, stir ultrasonically in a nitrogen atmosphere in the dark for 6-8 hours, filter, remove the filtrate, and finally dry in a dark vacuum at 30-35° C. until constant weight, and the preparation is completed.

[0015] Furthermore, the polyvinyl alcohol in step (2) is polyvinyl alcohol 1788.

[0016] Furthermore, the hydroxylated nano-silica in step (2) is prepared by the following steps:

[0017] Step A: Add 20-25 parts by weight of hydrogen peroxide, 10-15 parts by weight of ammonia water and 2-3 parts by weight of nano-silicon dioxide to 100 parts by weight of deionized water, then stir at 50-60° C. for 2-4 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 60-70° C. until constant weight, and the preparation is completed.

[0018] Preferably, the mass fraction of the ammonia water in step A is 20-25%.

[0019] Preferably, the particle size of the nano-silicon dioxide in step A is 10-20 nm.

[0020] Furthermore, the power of the ultrasound in step (2) is 300-400W.

[0021] As a preferred technical solution of the present invention, the basalt fiber in step X refers to a basalt fiber with a length of 6-8 mm and a diameter of 10-12 μm.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention creatively adds deionized water, polyvinyl alcohol, dopamine and hydroxylated nano-silica in a certain mass ratio to the recycled coarse aggregate obtained by conventional operations such as crushing, sorting and magnetic separation of construction waste, and then ultrasonically stirs the recycled coarse aggregate in a nitrogen atmosphere in the dark and dries it in a vacuum in the dark. Through the bonding of polyvinyl alcohol, the drying and precipitation of dopamine and the filling of hydroxylated nano-silica, a new type of reinforced recycled coarse aggregate is prepared, which is compounded with basalt fiber to form a composite material. After physical blending with cementitious material, fine aggregate, fly ash, mineral powder, deionized water and water reducing agent, concrete is obtained. The concrete not only has excellent mechanical strength, but also can completely replace natural coarse aggregate, and has very good market application prospects.

[0024] (2) The present invention creatively adds deionized water, polyvinyl alcohol, dopamine and hydroxylated nano-silica in a certain mass ratio to the recycled coarse aggregate prepared from construction waste, and then ultrasonically stirs the recycled coarse aggregate in a nitrogen atmosphere in the dark and dries it in a vacuum in the dark, thereby preparing a new type of reinforced recycled coarse aggregate, which is compounded with coupled basalt fiber to form a composite material; polyvinyl alcohol, as a commonly used binder, has a certain bonding ability and film-forming property, which can effectively repair the surface cracks of the recycled coarse aggregate, thereby reducing the water absorption rate and promoting the mechanical strength to a certain extent; dopamine, as a monomer that will self-polymerize under alkaline aerobic conditions, is dissolved-dried and precipitated. It can be deposited in the micro cracks of recycled coarse aggregate. According to the alkaline nature of concrete, dopamine will gradually polymerize to form polydopamine in the subsequent preparation process of concrete. Polydopamine has a very strong adhesion ability to most substances. It can act as a mediating layer to greatly promote the interface performance between recycled coarse aggregate and various components, thereby improving the mechanical strength of concrete. Nano-silica and basalt fiber are both introduced as reinforcing fillers. Among them, nano-silica is more effective in filling the tiny cracks of recycled coarse aggregate. At the same time, after hydroxylation, it can have a better synergistic effect with polydopamine and better interface performance.

[0025] (3) The concrete prepared by the present invention has excellent mechanical strength and does not require the addition of natural coarse aggregate, so the market application prospect is very good. DETAILED DESCRIPTION

[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0027] The construction waste in all embodiments and comparative examples of the present invention is waste C40 concrete; the particle size gradation of the recycled coarse aggregate is a continuous gradation of 5-31.5 mm, the continuous gradation meets the requirements of the standard GB / T 25177-2010, and the water absorption rate is 6.0%; the fly ash is purchased directly from the market, purchased from Inner Mongolia Langyi Environmental Protection Building Materials Co., Ltd., and the product name is secondary fly ash; the mineral powder is purchased directly from the market, purchased from Shijiazhuang Mayue Building Materials Co., Ltd., and the grade is S95; the polycarboxylate water reducer is purchased directly from the market, purchased from Henan Mingzhixin Chemical Products Co., Ltd., and the model is industrial grade; the P·O42.5 grade cement is purchased directly from the market, purchased from Tongchuan Shengwei Building Materials Co., Ltd.

[0028] Example 1

[0029] A method for preparing high-strength concrete based on construction waste, the preparation method comprising the following steps:

[0030] Step X: Add fine aggregate, composite material, fly ash and mineral powder to the cementitious material under the condition of contact with air, and then stir and mix at room temperature for 1 minute, then add deionized water and water reducing agent, and continue to stir and mix at room temperature for 3 minutes, and the preparation is completed; the composite material is a mixture of reinforced recycled coarse aggregate and basalt fiber.

[0031] The mass ratio of the cementitious material, the fine aggregate, the composite material, the fly ash, the mineral powder, the deionized water and the water reducing agent in step X is 270:715:1080:100:60:160:9.5.

[0032] The cementitious material in step X is cement; the cement is P·O42.5 grade cement.

[0033] The fine aggregate in step X is river sand; the fineness modulus of the river sand is 2.6.

[0034] The water reducing agent in step X is a polycarboxylate water reducing agent.

[0035] The mass ratio of the reinforced recycled coarse aggregate to the basalt fiber in step X is 100:1.

[0036] The reinforced recycled coarse aggregate in step X is prepared by the following steps:

[0037] (1) crushing, sorting, magnetic separation and screening the construction waste in sequence to obtain recycled coarse aggregate;

[0038] (2) Add 10 parts by weight of polyvinyl alcohol to 100 parts by weight of deionized water, and then stir at 90°C until completely dissolved, cool naturally to room temperature, then add 6 parts by weight of dopamine, 0.2 parts by weight of hydroxylated nano-silica and 30 parts by weight of recycled coarse aggregate, stir ultrasonically in a nitrogen atmosphere in the dark for 6 hours, filter, remove the filtrate, and finally dry in a dark vacuum at 30°C until constant weight, and the preparation is completed.

[0039] The polyvinyl alcohol in step (2) is polyvinyl alcohol 1788.

[0040] The hydroxylated nano-silica in step (2) is prepared by the following steps:

[0041] Step A: Add 20 parts by weight of hydrogen peroxide, 10 parts by weight of ammonia water and 2 parts by weight of nano-silicon dioxide to 100 parts by weight of deionized water, then stir at 50°C for 2h, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 60°C until constant weight, and the preparation is completed.

[0042] The mass fraction of the ammonia water in step A is 20%.

[0043] The particle size of the nano-silicon dioxide in step A is 10 nm.

[0044] The power of the ultrasound in step (2) is 300W.

[0045] The basalt fiber in step X refers to a basalt fiber with a length of 6 mm and a diameter of 10 μm.

[0046] Example 2

[0047] A method for preparing high-strength concrete based on construction waste, the preparation method comprising the following steps:

[0048] Step X: Add fine aggregate, composite material, fly ash and mineral powder to the cementitious material under the condition of contact with air, and then stir and mix at room temperature for 2 minutes, then add deionized water and water reducing agent, and continue to stir and mix at room temperature for 5 minutes, and the preparation is completed; the composite material is a mixture of reinforced recycled coarse aggregate and basalt fiber.

[0049] The mass ratio of the cementitious material, the fine aggregate, the composite material, the fly ash, the mineral powder, the deionized water and the water reducing agent in step X is 270:720:1085:100:62:160:10.

[0050] The cementitious material in step X is cement; the cement is P·O42.5 grade cement.

[0051] The fine aggregate in step X is river sand; the fineness modulus of the river sand is 2.6.

[0052] The water reducing agent in step X is a polycarboxylate water reducing agent.

[0053] The mass ratio of the reinforced recycled coarse aggregate to the basalt fiber in step X is 100:1.2.

[0054] The reinforced recycled coarse aggregate in step X is prepared by the following steps:

[0055] (1) crushing, sorting, magnetic separation and screening the construction waste in sequence to obtain recycled coarse aggregate;

[0056] (2) Add 12 parts by weight of polyvinyl alcohol to 100 parts by weight of deionized water, and then stir at 95°C until completely dissolved, cool naturally to room temperature, then add 6 parts by weight of dopamine, 0.3 parts by weight of hydroxylated nano-silica and 35 parts by weight of recycled coarse aggregate, stir ultrasonically in a nitrogen atmosphere in the dark for 8 hours, filter, remove the filtrate, and finally dry in a dark vacuum at 35°C until constant weight, and the preparation is completed.

[0057] The polyvinyl alcohol in step (2) is polyvinyl alcohol 1788.

[0058] The hydroxylated nano-silica in step (2) is prepared by the following steps:

[0059] Step A: Add 25 parts by weight of hydrogen peroxide, 15 parts by weight of ammonia water and 3 parts by weight of nano-silicon dioxide to 100 parts by weight of deionized water, then stir at 60°C for 4 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 70°C until constant weight, and the preparation is completed.

[0060] The mass fraction of the ammonia water in step A is 25%.

[0061] The particle size of the nano-silicon dioxide in step A is 20 nm.

[0062] The power of the ultrasound in step (2) is 400W.

[0063] The basalt fiber in step X is a basalt fiber with a length of 8 mm and a diameter of 12 μm.

[0064] Example 3

[0065] A method for preparing high-strength concrete based on construction waste, the preparation method comprising the following steps:

[0066] Step X: Add fine aggregate, composite material, fly ash and mineral powder to the cementitious material under the condition of contact with air, and then stir and mix at room temperature for 1.5 minutes, then add deionized water and water reducing agent, and continue to stir and mix at room temperature for 4 minutes, and the preparation is completed; the composite material is a mixture of reinforced recycled coarse aggregate and basalt fiber.

[0067] The mass ratio of the cementitious material, the fine aggregate, the composite material, the fly ash, the mineral powder, the deionized water and the water reducing agent in step X is 270:718:1082:100:61:160:9.7.

[0068] The cementitious material in step X is cement; the cement is P·O42.5 grade cement.

[0069] The fine aggregate in step X is river sand; the fineness modulus of the river sand is 2.6.

[0070] The water reducing agent in step X is a polycarboxylate water reducing agent.

[0071] The mass ratio of the reinforced recycled coarse aggregate to the basalt fiber in step X is 100:1.1.

[0072] The reinforced recycled coarse aggregate in step X is prepared by the following steps:

[0073] (1) crushing, sorting, magnetic separation and screening the construction waste in sequence to obtain recycled coarse aggregate;

[0074] (2) Add 11 parts by weight of polyvinyl alcohol to 100 parts by weight of deionized water, and then stir at 93°C until completely dissolved, cool naturally to room temperature, then add 6 parts by weight of dopamine, 0.25 parts by weight of hydroxylated nano-silica and 33 parts by weight of recycled coarse aggregate, stir ultrasonically in a nitrogen atmosphere in the dark for 7 hours, filter, remove the filtrate, and finally dry in a dark vacuum at 33°C until constant weight, and the preparation is completed.

[0075] The polyvinyl alcohol in step (2) is polyvinyl alcohol 1788.

[0076] The hydroxylated nano-silica in step (2) is prepared by the following steps:

[0077] Step A: Add 23 parts by weight of hydrogen peroxide, 12 parts by weight of ammonia water and 2.5 parts by weight of nano-silicon dioxide to 100 parts by weight of deionized water, then stir at 55° C. for 3 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 65° C. until constant weight, and the preparation is completed.

[0078] The mass fraction of the ammonia water in step A is 23%.

[0079] The particle size of the nano-silicon dioxide in step A is 15 nm.

[0080] The power of the ultrasound in step (2) is 350W.

[0081] The basalt fiber in step X refers to a basalt fiber with a length of 7 mm and a diameter of 11 μm.

[0082] Comparative Example 1

[0083] On the basis of Example 1, basalt fiber was replaced by reinforced recycled coarse aggregate of equal weight, and the rest remained unchanged.

[0084] Comparative Example 2

[0085] On the basis of Example 1, the polyvinyl alcohol in step (2) was replaced by an equal weight of deionized water, and the rest remained unchanged.

[0086] Comparative Example 3

[0087] On the basis of Example 1, dopamine in step (2) was replaced by an equal weight of deionized water, and the rest remained unchanged.

[0088] Comparative Example 4

[0089] On the basis of Example 1, the hydroxylated nano-silica in step (2) was replaced by an equal weight of deionized water, and the rest remained unchanged.

[0090] Comparative Example 5

[0091] Based on Example 1, the hydrogen peroxide and ammonia water in step A were replaced with deionized water of equal weight, and the rest remained unchanged.

[0092] Test Example 1

[0093] Strength test:

[0094] The high-strength concrete prepared in Examples 1-3 and Comparative Examples 1-5 were respectively made into test pieces with a size of 150 mm × 150 mm × 150 mm (the test molds used to make the test pieces conform to the provisions of standard GB / T50081-2002), and then the cube compressive strength test (28d) was carried out in accordance with standard GB / T 50081-2019.

[0095] Table 1. Strength test results

[0096] Cube compressive strength 28d / MPa Example 1 42.9 Example 2 44.0 Example 3 43.1 Comparative Example 1 38.7 Comparative Example 2 35.4 Comparative Example 3 38.0 Comparative Example 4 37.6 Comparative Example 5 39.5

[0097] From the comparison between Example 1 and Comparative Examples 1-5 in Test Example 1, it can be seen that the concrete prepared by the present invention can obtain excellent strength even if the coarse aggregates are all reinforced recycled coarse aggregates, and the cube compressive strength 28d reaches more than 40 MPa.

[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing high-strength concrete based on construction waste, characterized in that: The preparation method comprises the following steps: Step X: adding fine aggregate, composite material, fly ash and mineral powder to the cementitious material under the condition of contact with air, and then stirring and mixing at room temperature for 1-2 minutes, and then adding deionized water and water reducing agent, and continuing to stir and mix at room temperature for 3-5 minutes, so that the preparation is completed; the composite material is a mixture of reinforced recycled coarse aggregate and basalt fiber; The reinforced recycled coarse aggregate in step X is prepared by the following steps: (1) Crush, sort, magnetically separate and screen the construction waste in sequence to obtain recycled coarse aggregate; (2) Add 10-12 parts by weight of polyvinyl alcohol to 100 parts by weight of deionized water, stir at 90-95°C until completely dissolved, cool naturally to room temperature, then add 6 parts by weight of dopamine, 0.2-0.3 parts by weight of hydroxylated nano-silicon dioxide and 30-35 parts by weight of recycled coarse aggregate, stir ultrasonically in a nitrogen atmosphere in the dark for 6-8 hours, filter, remove the filtrate, and finally dry in a dark vacuum at 30-35°C until constant weight, and the preparation is completed; The hydroxylated nano-silica in step (2) is prepared by the following steps: Step A: Add 20-25 parts by weight of hydrogen peroxide, 10-15 parts by weight of ammonia water and 2-3 parts by weight of nano-silicon dioxide to 100 parts by weight of deionized water, then stir at 50-60° C. for 2-4 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 60-70° C. until constant weight, and the preparation is completed.

2. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: In step X, the mass ratio of the cementitious material, the fine aggregate, the composite material, the fly ash, the mineral powder, the deionized water and the water reducing agent is 270:715-720:1080-1085:100:60-62:160:9.5-10.

3. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: The cementitious material in step X is cement; the cement is P·O42.5 grade cement.

4. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: The fine aggregate in step X is river sand; the fineness modulus of the river sand is 2.

6.

5. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: The mass ratio of the reinforced recycled coarse aggregate to the basalt fiber in step X is 100:1-1.

2.

6. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: The polyvinyl alcohol in step (2) is polyvinyl alcohol 1788.

7. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: The mass fraction of the ammonia water in step A is 20-25%.

8. The method for preparing high-strength concrete based on construction waste according to claim 1, characterized in that: The basalt fiber in step X refers to a basalt fiber with a length of 6-8 mm and a diameter of 10-12 μm.

Citation Information

Patent Citations

  • Preparation method of rubber co-doped nano silicon dioxide modified recycled concrete

    CN113045270A

  • Nano silicon dioxide and basalt fiber synergistically enhanced recycled concrete and preparation method thereof

    CN114656206A

  • Recycled aggregate concrete as well as preparation method and application thereof

    CN116161925A

  • Carbonization-free building solid waste modified recycled coarse aggregate as well as preparation method and application thereof

    CN117800630A